Structural correlates of moral emotions in patients with schizophrenia (2023)
Patients with schizophrenia exhibit deficits in multiple domains of social cognition. However, no research has focused on examining moral emotions and their structural correlates in this clinical population. Therefore, the objective of this study was to investigate the neural correlates of envy and Schadenfreude (pleasure derived from the misfortune of others) in patients with schizophrenia and healthy controls. We recruited 27 patients diagnosed with schizophrenia and 38 healthy controls to complete a task designed to evoke Schadenfreude and envy. Additionally, we administered clinical and cognitive assessments to both groups. Age, sex, and premorbid intellectual level were paired between the groups. We obtained structural magnetic resonance imaging (MRI) measures from a subsample of 21 patients with schizophrenia and 27 healthy controls. Voxel-Based Morphometry was employed to explore the correlations between gray matter volumes and scores on the moral emotion test. The results revealed that patients reported significantly higher levels of envy compared to the control group. However, there were no significant differences in the experience of Schadenfreude. In patients, we observed that higher levels of envy were correlated with less gray matter volume in the middle temporal gyrus. Higher Schadenfreude scores were correlated with less grey matter volume in the postcentral gyrus, the inferior temporal gyrus and the cerebellum. These brain areas have been previously associated with social cognition, particularly mentalizing abilities. Overall, our findings contribute to a better understanding of alterations in social cognition in individuals with schizophrenia.